COMPETITIVENESS OF INDONESIAN TEA IN INTERNATIONAL MARKET - Jauhar Samudera; Arief Daryanto; Imam Teguh Saptono (School of Business, IPB University (SB-IPB), 2017)
Since 2000, Indonesian tea has experienced a lot of problems such as land use change of plantation, lower selling prices, and low productivity. The objectives of this study are to analyze the competitiveness of tea in Indonesia and formulate priority improvements that can support the increasing competitiveness of Indonesian tea. The methods used to analyze the competitiveness were the Revealed Comparative Advantage (RCA) and the Export Product Dynamics (EPD), and to formulate strategies to increase competitiveness, Importance Performance Analysis (IPA) was applied. Based on RCA, the types of Indonesian tea which have strong competitiveness are HS 090 210 and HS 090240. The EPD analysis showed that only tea of HS 090210 is in the rising star position, while the HS 090220, HS 090230 and HS090240 tea types are on the retreat position. Based on IPA, sub-determinants which are priority to improve are in quadrant A (under act) consisting of five sub-factors, namely the availability of human resources with the capbility of production management, marketing and possess an entrepreneurial spirit; availability and ease of access to capital; strengthening of the structure of Indonesian tea agribusiness; the government policies in improving domestic demand conditions and in encouraging the development of tea processing industry.Keywords: competitiveness, tea, RCA, EPD, IPA